2015
DOI: 10.1155/2015/850785
|View full text |Cite
|
Sign up to set email alerts
|

Ahmed Glaucoma Valve Implantation for Refractory Glaucoma in a Tertiary Hospital in Brazil

Abstract: Purpose. To evaluate the efficacy of Ahmed Glaucoma Valve (AGV) implantation in patients with refractory glaucoma in a tertiary hospital in Brazil. Methods. Retrospective case series of patients who underwent AGV implantation. Primary outcome was to assess the rate of failure, which was defined as intraocular pressure (IOP) in two consecutive visits greater than 18 or lower than 5 mmHg (criterion 1) or IOP greater than 15 or lower than 5 mmHg (criterion 2). The secondary outcome was to investigate risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…3839 In fact, the treatment with aqueous suppressant has been suggested by two recent prospective studies in the early postoperative period, while IOPs were still in the low-teens to reduce the incidence of IOP spikes associated with the hypertensive phase and improve the success rate. 4041 Despite being the most frequent early complication in our study, hypertensive phase was not a risk factor for surgical failure, both in the univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…3839 In fact, the treatment with aqueous suppressant has been suggested by two recent prospective studies in the early postoperative period, while IOPs were still in the low-teens to reduce the incidence of IOP spikes associated with the hypertensive phase and improve the success rate. 4041 Despite being the most frequent early complication in our study, hypertensive phase was not a risk factor for surgical failure, both in the univariate and multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent report by Perez et al [ 13 ] subjected patients to intraoperative and postoperative subconjunctival MMC injections in order to reduce the incidence of hypertensive phase (defined as IOP exceeding 21 mmHg during the first three postoperative months) among patients who underwent AC AGV implantation. Other studies have also highlighted the role of antifibrotic agents in reducing incidences of hypertensive phases in the past [ 12 , 19 , 20 ]. Even though the MMC group of the present study showed significantly lower IOP in the 1st postoperative month, when the definition of the hypertensive phase was adopted as mentioned above to calculate its rate in the two groups, no significant difference was noted ( p = 0.062).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of NVG consists of pharmacological treatment with IOP-lowering agents combined with surgical interventions. [1819] There is no consensus on the optimal surgery for this condition. Trabeculoplasty and trabeculectomy are known to increase filtration and reduce IOP.…”
Section: Discussionmentioning
confidence: 99%